2009
DOI: 10.1111/j.1610-0387.2009.07082.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life for patients with chronic venous insufficiency, present or healed leg ulcers

Abstract: Even though ulcer healing is an admirable goal, it does not necessarily lead to an improved QOL, probably because of the numerous comorbidities in this patient group. Nonetheless, it is important to control problems associated directly with the wound to allow ulcer patients to participate actively in everyday life and minimize social problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 15 publications
4
19
0
Order By: Relevance
“…22,23 A further step included in several studies was to examine the association of the clinical signs and symptoms with QoL and with the eco-Doppler assessment; 24 it was concluded that the frequency of venous reflux increases with the CEAP C grade. There are also publications examining the relationship between CEAP and QoL, 25,26 including some with apparently contradictory results, 27 showing no differences between the QoL of patients with healed and active ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 A further step included in several studies was to examine the association of the clinical signs and symptoms with QoL and with the eco-Doppler assessment; 24 it was concluded that the frequency of venous reflux increases with the CEAP C grade. There are also publications examining the relationship between CEAP and QoL, 25,26 including some with apparently contradictory results, 27 showing no differences between the QoL of patients with healed and active ulcers.…”
Section: Discussionmentioning
confidence: 99%
“…Renner et al 48 investigated changes in QoL for patients with chronic venous insufficiency (CVI) but without a history of ulceration, active, and healed leg ulcers due to CVI. They demonstrated by using the FLQA-w that in patients with active or healed ulceration pain assessment, physical complaints, and differences in everyday life are mostly agedependent but not dependent on the status of their leg ulcer.…”
Section: Depression and Wound Closurementioning
confidence: 99%
“…However, there are also reports which do not seem as enthusiastic. Renner et al [15] did not find a statistically significant improvement in QoL even in patients (treated with compression garments) who had healed ulcerations. They attributed the result to the numerous comorbidities in the studied group.…”
Section: Discussionmentioning
confidence: 91%
“…Psychological problems are common in patients with CVD, most often taking the form of anxiety, depression, low self-esteem, and social exclusion [12]. These issues are often ignored during traditional therapeutic procedures [13][14][15], whereas the full knowledge about the patient and their attitude to the disease and to the proposed treatment has a tremendous influence on maintaining the patient's compliance [10]. In this study, we observed that regular, properly performed short-term compression therapy significantly improved QoL in all its aspects in patients suffering from CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation